A comparative study on attitudes towards SMS advertising and mobile application advertising. (2017) - Aydin, Gökhan; Karamehmet, Bilge
The objective of the present study is to determine the major factors influencing consumers' attitudes towards two major types of mobile marketing activities: SMS advertising and mobile application advertising. It also discusses the potential differences in antecedents of attitude between the two types of advertisements. The study was carried out in Turkey among university students, who are commonly targeted in mobile marketing studies due to their high mobile phone ownership rates and familiarity with new technologies. A total of 489 valid questionnaires were obtained and analysed using partial least squares structural equation modelling. The findings indicate that overall attitudes towards both mobile advertisement types are negative, SMS marketing being the inferior type. Differences in perceptions of the antecedents of attitudes towards SMS and mobile app ads were detected. On the other hand, the way variables affect attitudes (paths) among the two wireless advertisements types were quite similar.